ASEAN Norms and Gender-Responsive Human security - Kim, Hyung-Jong; Arnakim, Lili Yulyadi; Prihatini, Ella Syafputri; Dewi, Galuh Dian Prama (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2023)
The Association of Southeast Asian Nations (ASEAN) has instrumentalized gender equality to present itself as a responsible regional organization accommodating universal norms. However, there is an ontological gap between ASEAN and UN-led programs derived from the inconsistency between intrinsic and extrinsic motivation toward universal norms. This study argues that the inefficiency of ASEAN in pursuing gender equality is primarily attributed to the practice matter of ASEAN. Using primary and secondary data collected through various means, this paper finds that ASEAN efforts on gender equality were mainly raised in declarations and conferences. ASEAN is a particularly important agent in promoting gender-responsive human security, given the nature of challenges and the political and economic limitations of ASEAN member states. It also tends to be a good global citizen as a norm entrepreneur by promoting universal norms and involving global programs led by the UN, such as Millennium Development Goals (MDGs) and Sustainable Development Goals (SDGs). Keywords: ASEAN norms, ASEAN community, gender equality, human security, and norm entrepreneur Association of Southeast Asian Nations (ASEAN) telah melembagakan kesetaraan gender untuk menampilkan dirinya sebagai organisasi regional yang bertanggung jawab mengakomodasi norma-norma universal. Namun, terdapat kesenjangan ontologis antara program-program yang dipimpin ASEAN dan PBB, yang berasal dari inkonsistensi antara motivasi intrinsik dan ekstrinsik terhadap norma-norma universal. Studi ini berpendapat bahwa inefisiensi ASEAN dalam mengejar kesetaraan gender sebagian besar dikaitkan dengan masalah praktik ASEAN. Dengan menggunakan data primer dan sekunder yang dikumpulkan melalui berbagai sumber, makalah ini menemukan bahwa upaya ASEAN dalam kesetaraan gender secara umum diangkat dalam deklarasi dan konferensi. ASEAN adalah agen yang sangat penting dalam mempromosikan keamanan manusia yang responsif gender, mengingat sifat tantangan dan keterbatasan politik dan ekonomi negara-negara anggota ASEAN. Hal ini juga cenderung menjadi warga dunia yang baik sebagai norm entrepreneur dengan mempromosikan norma-norma universal dan melibatkan program global yang dipimpin oleh PBB seperti Millennium Development Goals (MDGs) dan Sustainable Development Goals (SDGs). Kata-kata kunci: ASEAN norms, komunitas ASEAN, kesetaraan gender, keamanan manusia, dan norm entrepreneur